Transcriptomic and Proteomic Study on the High-Fat Diet Combined With AOM/DSS-Induced Adenomatous Polyps in Mice - Guo, Cui; Xu, Yimin; Han, Xinyue; Liu, Xiaoqiang; Xie, Runnan; Cheng, Zhihong; Fu, Xiaoling (Frontiers in Oncology, 2021)
Objective: To screen and identify targets and bacteria genus leading to adenomatous polyps in mouse induced by high-fat diet (HFD) +AOM/DSS using omics technology. Methods: The targets of colorectal adenoma disease were obtained from the GeneCards and OMIM database. The SPF C57BL mice were randomly divided into blank group (Control) and colorectal adenoma model (AOM/DSS+HFD, ADH) groups. The model group was intraperitoneally injected with AOM reagent. Then, mice was given with 2.5%DSS (in free drinking water) and high-fat diet to establish the ADH model. During this period, the changes of physical signs of mice in each group were observed. After the end of modeling, HE staining was used to evaluate the histopathological change of mice. The differentially expressed genes and proteins in the Control group and ADH group were detected by RNA-seq transcriptome sequencing and Tandem Mass Tags (TMT) quantitative proteomics. The histological results were analyzed by intersection with the intestinal adenoma targets obtained from the database. Moreover, the changes of intestinal flora in the two groups were examined. The correlation between targets and differential bacteria was analyzed and verified by Parallel Reaction Monitoring (PRM) to comprehensively evaluate the mouse model of adenomatous polyp induced by AOM/DSS+HFD. Results: The general condition and histopathological results of mice proved that the ADH mouse model was established and tubular adenoma was formed. A total of 604 genes and 42 proteins related to intestinal adenoma were obtained by histological analysis and database intersection analysis. The intestinal microflora of normal mice was significantly different from that of ADH mice, and the constituents and abundance of intestinal flora were similar to those of human intestinal adenoma. GATA4 and LHPP were selected as potential pathological markers of model mice by correlation analysis of targets and intestinal flora. Conclusion: The pathological results, molecular pathological markers and the changes of intestinal flora reflect that the mouse ADH model is ideal for studying the transformation of inflammatory cancer. The ADH model will be helpful for understanding the occurrence and development of human colorectal cancer.